Implementation of Branding and Digital Marketing Strategies for Tempe Chips Business in Sawoo Village Ponorogo - Kenlies Era Rosalina Marsudi; Aditya Farhan Romadloni; Meiasya Putri Rosanti; Meliana Viska Antari; Muhammad Azizul Ashar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The use of technology and the internet in the current era is increasingly developing in various fields, including UMKM in running their businesses. The use of digital technology makes it easier for UMKM, especially in forming product images and marketing these products on social media. However, a lack of understanding regarding product branding and digital marketing by UMKM hinders the development of their businesses. Therefore, the aim of this community service is focused on increasing sales of K-Ngen Tempe Chips UMKM products located in Sawoo Village, District. Sawoo, Kab. Ponorogo. The method used in this research is ABCD (Asset Based Community Development) which is applied through several steps including discovery, design, define, and reflection. With this activity, it is hoped that business actors can understand the use of digital marketing and social media in accordance with current developments and market needs that consumers are interested in in the current era. So that producers can increase sales value and expand product marketing and have product packaging skills that attract consumer purchasing power.